(3GdRjL GdLOjO dGdZ Hjcs - (3eMeO Hf GHi GdaJM GdUhai GdeUQjs; (3eMeO Hf TGgQ Hf JjehQ GdZ Hc,J (B853 (3g` s
(3ChdgG (B:s
(3GdJGQjN gh hbJ eTghQ jfSH Edjg GdReGf GdCJi HYOg hdeG cGfJ GdJhGQjN cKjQI cGf GTQagG JGQjN GdYQH s
(3BNQgG (B:s
(3hEdG aGfbUg jMUd eWGdY GdWGdY MUd HgG GdWGdY hGdYTQ ceG JbOe hGddg JYGdi GYde HGdZjH s
(3HgG LOGhd cKjQI hCTcGd gfOSjIs
(3QHeG Jchf gPg GdfSNI gi eShOg GdeDda dCfg JLGgd ajgG GdHSedI hHOC HGdehVhY eHGTQIs
(3JTJed GdfSNI Ydi GdYOjO ef GdLOGhd hGdUhQ GdgfOSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B966s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs